The Comparison Effect of Nickel (II) and Cadmium (II) Complexes with Aqueous Extract of Tecrium polium.L (Ja,adah) Plant on Hepatocellular Carcinoma Cell Line HeP2 (Baghdad Science Journal, 2025)
Cancer stay to be one of the leading causes of death throughout the world due to a limited success to use treatments. The new synthesized metal complexes with formula: [Ni L2 (H2O)2]. 2.5 E t OH and [Cd L2]. ½ H2O Where L = Bis [ 5 – ( P – nitrophenyl ) - 4 – phenyl 1 , 2 , 4 – trazol – 3 – dithiocarbamato hydrazide ] and the aqueous extract of Teucrium polium L.(TP) plant (Ja,adahin Arabic) were examined against growth cells of hepatocellular Carcinoma cell Line ( HeP2 ). The cytotoxicity assay of cancer cell line was used for determination of inhibition rate with three concentrations; (62.5, 105 and 250 µg /200µl). The aqueous extract of TP plant induced death of cancer cells by significant elevation of the inhibition rate to 50.03% while the cytotoxic effect of Ni ( II ) complex reached 45.77% and Cadmium (II) was 35.73% at 125µg /200µl.The present study indicates that there are no significant differences between the two new complexes Nickel(II) and Cadmium(II) compared with anticancer drug Cis-pt for all doses